Editorial: We continue our commitment to you (Revista Venezolana de Salud Pública, 2018)
The role of Public Health is increasingly important in Medical Sciences. Its field of action extends rapidly and broadly since its duty is to study and explain the causal behavior of a growing and diverse group of pathologies in population groups. The relevance of their contribution can also be explained by their contribution to public health policies, since numerous research studies are being promoted, generating relevant information for collective health decision-making. In this sense, the Revista Venezolana de Salud Pública continues to add to this scientific contribution promoting research in areas of great interest and relevance.